PRIMAL CUT CARCASS OF BALI BOAR WERE GIVEN FEED BASED ON CORN AND POLLARD WITH AMINOVIT SUPPLEMENTATION - R.O.E., Putri; Sumadi, I K.; Sriyani, N. L. P. (Jurnal Peternakan Tropika, 2019)
This research aims to know the effect of mixture of lysine, methionine supplementation and kolin in corn and pollard against primal cut carcass piece of bali boar. The research was conducted in BanjarBatuParas, Padang Sambian kaja village, West of Denpasar with long research of 12 weeks. Pigs were used in this research amount is 9 bali boar with average initial weight 13.11 kg. The design used in this study was a Design Randomized Complete with 3 treatments and 3 replicates. The treatment is given a bali boar rations without supplementation lysine, methionine and kolin (P0), bali boar given rations with a mixture of lysine, methionine supplementation and kolin 0.5% level (P1) and bali boar given rations with supplementation a mixture of lysine, methionine and kolin with level 1% (P2). The variables observed in this research is the primal cut carcass piece which covers the jowl, boston, loin, ham, picnic soldier and bacon belly. The results of this research show that the existence of the effect on the pieces of primal cut carcass of bali boar. Based on the results of the study it can be concluded that the provision of ration with aminovite supplementation (lysine, methionine and choline) was 0.5% and 1% significantly in increasing the primal percentage of carcasses of jowl and loin. But at the jowl portion of the primal carcass, 0.5% aminovite supplementation produced a higher percentage than 1% aminovite supplementation. Supplementation of 1% aminovite significantly increased the primal cut of the ham carcass. Key words: bali boar, primalcarcass, supplementation, aminovit